EVOLUTIONS IN THE NATIONAL AND THE EUROPEAN UNION BUSINESS ENVIRONMENT IN THE CONTEXT OF GLOBALIZATION - Alina HAGIU; Marinela BARBULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The paper supposes a systematic research and few pragmatic guidelines in addressing the competitive environment (national and European) in which are operating Romanian companies, because their work is heavily influenced by the business environment and determined by the factors of it. The business environment is characterized by a special dynamic, due to changes that occur within it, especially under the impact of scientific and technical revolution that has brought to the fore the knowledge as essential element of achieving a high competitiveness. We tried to argue the need for a strategic analysis of business environment in the context of globalization, we made an analysis of current status of the Romanian business environment compared to the other European Union member states, we have outlined several measures that should be implemented to contribute to the stability and to improving the Romanian business environment and we also realized a short analisys of the Romanian economy position in the international rankings.